Factors affecting bird richness in a fragmented cork oak forest in Morocco - Cherkaoui, Imad; Selmi, Slaheddine; Boukhriss, Jihen; Hamid, Rguibi-Idrissi; Mohammed, Dakki (Acta Oecologica, 2009)
The cork oak forest of Ma’amora in north-western Morocco was the largest cork oak forest in the world until the beginning of the 20th century. Due to growing land use for agriculture and urbanization, however, this forest has become fragmented into relatively small and isolated patches. The effects of this fragmentation on the diversity of wild animal communities have never been investigated despite the importance of such investigations in elaborating longterm conservation plans of the biodiversity of this forest system. In this study of a sample of 44 forest patches we assessed the relationships between species numbers of wintering, breeding and spring migrant birds and patch size, shape, isolation and vegetation structure. We found that species richnesses of the three studied bird assemblages were strongly related to local vegetation structure, namely to the diversity and abundance of trees and bushes. Patches with higher diversity and cover of trees and bushes support higher numbers of bird species. However, patch size, shape and isolation were not signiﬁcant predictors of bird richness. These results suggest that bird communities in the studied forest patches were more likely shaped by local habitat suitability rather than the amount of habitat or patch isolation. The results also demonstrate negative effects of current human pressures, namely logging, grazing and disturbance, on the diversity of bird communities in this forest system. This emphasizes the need for urgent management efforts aiming at reducing the negative impacts of forest use by humans on bird diversity in this forest system
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: birds; Cork Oak Forest; fragmentation; Morocco

Factors affecting bird richness in a fragmented cork oak forest in Morocco - Cherkaoui, Imad; Selmi, Slaheddine; Boukhriss, Jihen; Hamid, Rguibi-Idrissi; Mohammed, Dakki (Acta Oecologica, 2009)
The cork oak forest of Ma’amora in north-western Morocco was the largest cork oak forest in the world until the beginning of the 20th century. Due to growing land use for agriculture and urbanization, however, this forest has become fragmented into relatively small and isolated patches. The effects of this fragmentation on the diversity of wild animal communities have never been investigated despite the importance of such investigations in elaborating longterm conservation plans of the biodiversity of this forest system. In this study of a sample of 44 forest patches we assessed the relationships between species numbers of wintering, breeding and spring migrant birds and patch size, shape, isolation and vegetation structure. We found that species richnesses of the three studied bird assemblages were strongly related to local vegetation structure, namely to the diversity and abundance of trees and bushes. Patches with higher diversity and cover of trees and bushes support higher numbers of bird species. However, patch size, shape and isolation were not signiﬁcant predictors of bird richness. These results suggest that bird communities in the studied forest patches were more likely shaped by local habitat suitability rather than the amount of habitat or patch isolation. The results also demonstrate negative effects of current human pressures, namely logging, grazing and disturbance, on the diversity of bird communities in this forest system. This emphasizes the need for urgent management efforts aiming at reducing the negative impacts of forest use by humans on bird diversity in this forest system
Keywords: birds; Cork Oak Forest; fragmentation; Morocco